Learning to teach realistic mathematics in Vietnam - Nguyễn, Thanh Thủy (Printpartner Ipskamp B,V., 2005)
The book is tried to contribute to talk about the notions of teaching and learning with a students-centered approach for Vietnamese secondary education, to Vietnamese mathematics student teachers; and to develop a conceptual framework for learning to teach, to be introduced to Vietnamese mathematics teacher education.